Shock compressibility and spall strength of textolite depending on fiber orientation - Mochalova, V.M.; Utkin, A.V.; Rykova, V.E.; Endres, M.; Hoffmann, D.H.H. (Archives of Mechanics, 2019)
The experimental study of shock wave compressibility and spall strength of an aramid fiber reinforced epoxy composite (textolite) for two fiber orientations was performed by the VISAR interferometer. The particle velocity profiles were obtained at velocities of the flyer plate from 0.65 to 5.05 km/s. The sound speed of textolite for the longitudinal direction is three times higher than that for transverse one, and as a result, the particle velocity profiles are different for two orientations. For the transverse direction of the fibers, a single shock wave is observed, while for longitudinal one, a two-wave configuration is recorded up to 20 GPa. Hugoniot parameters for both orientations of the fibers were found up to 35 GPa: D = 2.37 + 1.26 ∗ u – for transverse one and D = 1.45 + 2.05 ∗ u – for longitudinal, where D is the shock wave velocity and u is the particle velocity. The spall strength of textolite is equal to 61 MPa for shocks traveling along the fibers, and this is almost twice higher than that for the transverse direction.